Growth attainment in extremely preterm children-has it changed over time? the epicure 2 study. (7th June 2011) - Chisholm, P; Moore, T; Haider, S; Hennessy, E; Johnson, S; Marlow, N
Abstract : Background: Children born extremely preterm have poor growth attainment; it is not known whether recent advances in neonatal care have led to an improvement. Aim: To compare SD scores of growth parameters at 35 months corrected age for children born ≤25 weeks in England in 1995 (EPICure) and 2006 (EPICure-2). Methods: Measures of height (ht), weight (wt), head circumference (HC) and mid upper arm circumference (MUAC) were taken as part of a neurodevelopmental assessment. Body mass index (BMI) and SD scores were calculated using British Growth Foundation normative data. Results: In 2006 325/586 (55%) of survivors ≤25 week were seen, of whom 98% had growth measures. Weight, height, MUAC and BMI were all significantly improved at 35 months corrected age compared to the 1995 EPICure cohort (table 1 ). There was no significant difference in HC. Improvement in weight gain was due to greater post-discharge growth. Conclusion: There has been a significant improvement since 1995 in all growth parameters except HC at 35 months corrected age. Improved weight gain at 35 months was attributable to post-discharge catch-up growth.